2009
DOI: 10.1111/j.1439-0272.1976.tb01645.x
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of Fertility Disorders by Detection and Treatment of Varicocele at School and College Age

Abstract: Zusammenfassung Vorbeugung von Fertilitätsstörungen durch frühzeitige Diagnostik und Behandlung der Varikocele bei Schülern und Studenten 4,067 Schüler und Studenten (12 ‐ 15 Jahre) wurden auf das Vorhandensein einer linksseitigen Varikozele untersucht. Mit dem Einsetzen der Pubertät steigt die Häufigkeit von Varikozelen stufenweise an und bleibt danach konstant. In der gesamten Gruppe liegt die Frequenz bei 14.7%. Nur die Gruppen mit Varikozelen zweiten und dritten Grades können als “Risikogruppe” bezeichnet … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
47
1
9

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 238 publications
(58 citation statements)
references
References 9 publications
0
47
1
9
Order By: Relevance
“…Varicoceles affect 15 % of adolescent males, similar to the incidence reported in healthy adult men [3]. The major concern for patients with a varicocele is infertility; with a varicocele present in 25-69 % of adults evaluated for infertility [4,5].…”
Section: Introductionmentioning
confidence: 82%
“…Varicoceles affect 15 % of adolescent males, similar to the incidence reported in healthy adult men [3]. The major concern for patients with a varicocele is infertility; with a varicocele present in 25-69 % of adults evaluated for infertility [4,5].…”
Section: Introductionmentioning
confidence: 82%
“…Scrotal varicocoeles commonly appear in early puberty during the growth spurt (Preston et al, 2008). These ectatic and tortuous veins of the pampiniform plexus are found in ca 12-15% of male adolescents, with a marked left-sided predominance of 90% (Steeno et al, 1976). Varicocoeles are rarely evident before early adolescence clinically.…”
Section: Introductionmentioning
confidence: 99%
“…Varicocoeles are rarely evident before early adolescence clinically. However, it is believed that the population of boys with varicocoeles represents the same population of adults with varicocoeles (Steeno et al, 1976). Although varicocoeles appear during adolescence, the pathophysiology of varicocoele remains uncertain.…”
Section: Introductionmentioning
confidence: 99%
“…5,6 Varicocele has been shown not to begin at adulthood, but more likely at adolescence or childhood. Two large studies by Oster 7 and Steeno et al 8 showed the incidence of varicoceles before adulthood at 16.2% and 14.7%, respectively. The term varicocele refers to varicose veins affecting the testicle, when the valves of the veins are incompetent and leaking with backflow.…”
mentioning
confidence: 98%